Society of Flavor Chemists newsletter, May 1981 - Society of Flavor Chemists (1981)
May 4, 1981 issue of the Society of Flavor Chemists newsletter.
Keywords: Society of Flavor Chemists; Newsletters; Flavoring essences; Flavoring essences industry; Flavor; Food additives; Food additives industry; Wine--Flavor and odor; Minutes (Records)